Ultrafast all-optical coherent control of single silicon vacancy colour centres in diamond - Jonas Nils Becker (Nature Portfolio, 2016)
All-optical coherent control schemes offer well-localized and ultrafast control of individual qubits in many-qubit systems. Here the authors report on all-optical resonant and Raman-based control of single silicon vacancies using picosecond pulses, much faster than the ground state coherence time.